Investigating the effect of seed coating with biochar and activated carbon on some indicators of germination and vigor of quinoa (Chenopodium quinoa) under salinity stress - Parimah Shokouhi Nasab; Hamidreza Balouchi; َAli Moradi; Mohsen Movahhedi Dehnavi (علوم و فناوری بذر ایران, 2024)
This experiment was conducted in order to investigate the effect of seed coating with biochar and activated carbon on some quinoa seed germination indicators, and it was implemented as a factorial in the form of a completely randomized design with four replications in 2019, in Yasouj University's Faculty of Agriculture. The first factor is seed coating in four levels (no coating, coating with activated carbon, coating with biochar and coating with activated carbon + biochar) and the second factor includes salinity stress in four levels (zero, 75, 150 and 225 mM sodium chloride). The results of the interaction of salinity stress and seed coating showed that the highest content of soluble sugar (28.578 mg/g seed FW) and malondialdehyde (2.97 µmol/g seed FW) was obtained by coating with activated carbon in 150 mM salinity stress. Also, the highest amount of seed hydrogen peroxide (0.18 μmol/g seed FW) and proline (10.49 μmol/g seed FW) at the level of 225 mM sodium chloride was obtained by covering the seeds with biochar and active carbon, respectively. Covering seeds with activated carbon and biochar led to an increase in the length of root and shoot under salt stress conditions. However, under salinity stress conditions, root weight and length vigor index of seed improved more by coating seeds with activated carbon. It can be stated that seed coating can greatly reduce the harmful effects of osmotic stress on germination and biochemical traits in quinoa seedlings and improve seedling growth.